Coverage of intermittent preventive treatment of malaria in pregnancy in four sub-Saharan countries: findings from household surveys. (8th December 2020) - Pons-Duran, Clara; Llach, Mireia; Sacoor, Charfudin; Sanz, Sergi; Macete, Eusebio; Arikpo, Iwara; Ramírez, Máximo; Meremikwu, Martin; Mbombo Ndombe, Didier; Méndez, Susana; Manun'Ebo, Manu F; Ramananjato, Ranto; et al.
Abstract: Background: Intermittent preventive treatment in pregnancy (IPTp) with sulphadoxine-pyrimethamine (SP) is a key malaria prevention strategy in areas with moderate to high transmission. As part of the TIPTOP (Transforming IPT for Optimal Pregnancy) project, baseline information about IPTp coverage was collected in eight districts from four sub-Saharan countries: Democratic Republic of Congo (DRC), Madagascar, Mozambique and Nigeria. Methods: Cross-sectional household surveys were conducted using a multistage cluster sampling design to estimate the coverage of IPTp and antenatal care attendance. Eligible participants were women of reproductive age who had ended a pregnancy in the 12 months preceding the interview and who had resided in the selected household during at least the past 4 months of pregnancy. Coverage was calculated using percentages and 95% confidence intervals. Results: A total of 3911 women were interviewed from March to October 2018. Coverage of at least three doses of IPTp (IPTp3+) was 22% and 24% in DRC project districts; 23% and 12% in Madagascar districts; 11% and 16% in Nigeria local government areas; and 63% and 34% in Mozambique districts. In DRC, Madagascar and Nigeria, more than two-thirds of women attending at least four antenatal care visits during pregnancy received less than three doses of IPTp. Conclusions: The IPTp3+ uptake in the survey districts was far from the universal coverage. However, one of the study districts in Mozambique showed a much higher coverage of IPTp3+ than the other areas, which was also higher than the 2018 average national coverage of 41%. The reasons for the high IPTp3+ coverage in this Mozambican district are unclear and require further study.